Investigating Factors Affecting the Low Uptake of Insurance Institute of South Africa (IISA) Membership Among Insurance Professionals in Botswana. - Malambo, Maalila (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This study investigates the factors contributing to the low uptake of Insurance Institute of South Africa (IISA) membership among insurance professionals in Botswana. The goal is to comprehend this phenomenon and provide insights into improving membership rates. Design / Methodology / Approach: A questionnaire-based survey targeting insurance professionals, students, and lecturers was employed. This approach aimed to gather comprehensive perspectives on membership uptake and related factors. The survey identified primary influences on low membership uptake, including lack of awareness, high fees, perceived limited value, and inadequate networking opportunities. The study explored the importance of membership, benefits, barriers, and suggestions for boosting participation. Findings: The study reveals crucial factors contributing to low IISA membership rates. Challenges include insufficient awareness of benefits, high fees deterring potential members, perceived value gaps, and limited networking prospects. These insights provide a holistic understanding of obstacles faced by insurance professionals in joining IISA. The research underscores the significance of professional organization membership for networking, skill enhancement, and career growth. However, financial, and perceptual barriers hinder potential members from joining.